MANAJEMEN LABA DAN ETIKA BISNIS - Krismiaji . (Akademi Akuntansi YKPN Yogyakarta, 2012)
Earnings management is not a new in business practices. Many ways and motives are owned by managers. There are some controversy about earnings management. Some argue that earnings management have negative impacts to the reliability and credibility of accounting information. The other argue that earnings management is one of methods to arrange reported income in order to avoid the sharp fluctuation of reported income from time to time. This paper discuss earnings management from ethics perspective. The result shows that earnings mangement practice is depend on management intention. If it is done based on opportunistic motive, it will cost the other people, and this is not an ethical practice and vice versa. To ensure that earnings management practice will not break the ethics and even enhance usefullness of accounting information, organization can apply a more tight accounting standard and corporate governance.Keywords: Earnings Management, Ethics, Accounting Standard, Corporate Governance